Las desapariciones de personas en México: un estudio del fenómeno desde una perspectiva regional. El caso de Coahuila (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
This article aims to highlight the importance of analyzing regional contexts to determine more clearly the profile of disappearances and enforced disappearances that have developed during the Mexican “War on Drugs”. It will address the North-eastern Mexican state of Coahuila, where this crime was perpetrated by both paramilitary criminal organizations and state authorities in a context of corruption and impunity.
Keywords: enforced disappearance; War on Drugs; human rights; Mexico; Coahuila